Efektivitas Pembelajaran Game Based Learning Menggunakan Baamboozle Terhadap Prestasi Belajar Ekonomi Siswa Kelas XI SMAN 1 Kalitidu - Adelia, I’is; Astuti, Rika Pristian Fitri; Puspananda, Dian Ratna (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2025)
This study aims to examine the impact of a game-based learning model utilizing the Baamboozle platform on students’ academic achievement in Economics. A quantitative approach was employed using a quasi-experimental design, specifically the One-Group Pretest-Posttest Design. The participants consisted of 34 eleventh-grade students from SMA Negeri 1 Kalitidu. Data collection techniques included learning outcome tests (pretest and posttest), classroom observations, and documentation. Descriptive statistical analysis revealed an increase in students’ average scores from 51.32 (pretest) to 88.09 (posttest). The normality test confirmed that the data were normally distributed (sig. = 0.200), and the paired sample t-test indicated a statistically significant difference between pretest and posttest scores (sig. = 0.001, p < 0.05). Additionally, the average gain score of 0.76 fell into the high category, signifying a substantial improvement in learning outcomes. These findings suggest that implementing game-based learning through Baamboozle significantly enhances students’ academic performance and can serve as an effective, engaging instructional strategy aligned with the demands of modern education.